Analisis Pengaruh Return On Investment Terhadap Pofitabilitas Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia - Tan, Hendra (Ali Institute of Research and Publication, 2024)
The aim of this research is to determine whether Return On Investment has an effect on the profitability of manufacturing companies listed on the Indonesia Stock Exchange. This research consists of the return on investment variable as the independent variable and company profits as the dependent variable. The data analyzed are the company's annual financial reports for the period 2018 to 2023. From the research results it is known that Return On Investment shows an alpha coefficient value of 5% (t-stat = 4,448 > 1,667) and prob. 0.015 <0.05. Based on the research results, the hypothesis is accepted, namely that Return On Investment has a significant effect on the level of profits in manufacturing companies listed on the Indonesia Stock Exchange for the 2018-2023 period.